Effect of Activator Type on Geopolymer Mortars Containing Different Types of Fly Ash - Akyüncü, Veysel; Avşar, Yunus Emre; Emre, Tolga Enes (Periodica Polytechnica Civil Engineering, 2023)
In this study, the influence of the activator type on the physical and mechanical properties of the geopolymer mortars was analyzed. C and F-class fly ash (FA), blast furnace slag (BFS), sodium hydroxide (NH), sodium metasilicate (NS), standard sand, and distilled water were used in the production of mortar specimens. All specimens were cured at room temperature. C and F-class fly ash usage ratios are 0%, 15%, and 30%. NH was used as an activator in the 1st group of the produced geopolymer mortars, and NS with NH was used in the 2nd group. 5 series were produced and a flow-table test, ultrasonic pulse velocity test, flexural strength test, compressive strength test, and Scanning Electron Microscope-Energy Dispersive Spectrometry (SEM-EDS) microstructure analysis were applied to the samples. The addition of NS increased the compressive strength and the greatest increase occurred in the reference sample by 113%. It also increased the compressive strength of FAF30 by 60% in comparison to FAC30. Following the results of the SEM examination, when the reference samples were compared, the addition of NS inhibited the formation of cracks. According to the SEM-EDS analysis results, an increase in the F and C-class FA ratio improved the crack formation. Compared to F-class FA, FAC30 has more cracks due to the lower SiO2 content in C-class FA. High K content and SiO2 ratio, as determined by EDS analysis, boost the alkalinity and positively impact the strength.